Enhancing Students’ Awareness of Pubertal Signs and The Habit of Gratitude Through a Problem-Based Learning (PBL) Approach - Nurhasanah; Chusni, Muhammad Minan (Department of Teacher Professional Education, Tarbiya and Teacher Training Faculty, UIN Sunan Gunung Djati Bandung, 2025)
This study aims to enhance students’ understanding of the signs of puberty and develop responsible attitudes through the implementation of a Problem-Based Learning (PBL) approach. Conducted as Classroom Action Research (CAR), the study involved two learning cycles comprising planning, action, observation, and reflection stages. The participants were twelve fourth-grade students at SDN 2 Margajaya. Data were collected through comprehension tests, attitude observations, and interviews. The findings indicate that the use of PBL effectively improved students’ comprehension of pubertal changes and fostered more responsible behavior. Students demonstrated greater engagement during group discussions, completed tasks more independently, and showed increased empathy toward their peers. The application of PBL encouraged active learning, critical thinking, and moral awareness relevant to students’ developmental stages. This study highlights the potential of PBL as an effective pedagogical model in Islamic education to integrate cognitive and character development. By connecting learning materials about human growth with moral values such as gratitude and responsibility, PBL helps students understand personal changes as part of God’s creation, thereby strengthening their spiritual and social maturity.